In situ X-ray diffraction computed tomography studies examining the thermal and chemical stabilities of working Ba0.5Sr0.5Co0.8Fe0.2O3−δ membranes during oxidative coupling of methane. Issue 34 (29th June 2020) - Matras, Dorota; Vamvakeros, Antonis; Jacques, Simon D. M.; Middelkoop, Vesna; Vaughan, Gavin; Agote Aran, Miren; Cernik, Robert J.; Beale, Andrew M.
Abstract : In situ XRD-CT and post-reaction SEM/EDX were used to study the solid-state chemistry and structural changes of Ba0.5 Sr0.5 Co0.8 Fe0.2 O3− δ membrane reactors during the oxidative coupling of methane reaction. Abstract : In this study we present the results from two in situ X-ray diffraction computed tomography experiments of catalytic membrane reactors (CMRs) using Ba0.5 Sr0.5 Co0.8 Fe0.2 O3− δ (BSCF) hollow fibre membranes and Na–Mn–W/SiO2 catalyst during the oxidative coupling of methane (OCM) reaction. The negative impact of CO2, when added to the inlet gas stream, is seen to be mainly related to the C2+ yield, while no evidence of carbonate phase(s) formation is found during the OCM experiments. The main degradation mechanism of the CMR is suggested to be primarily associated with the solid-state evolution of the BSCF phase rather than the presence of CO2 . Specifically, in situ XRD-CT and post-mortem SEM/EDX measurements revealed a collapse of the cubic BSCF phase and subsequent formation of secondary phases, which include needle-like structures and hexagonal Ba6 Co4 O12 and formation of a BaWO4 layer, the latter being a result of chemical interaction between the membrane and catalyst materials at high temperatures.